The Meaning of Entrepreneurial Journalism Among Journalists of Mass Media Companies - Vazza, Agung Pragitya; Mulyana, Ahmad (Fakultas Dakwah UIN Saizu Purwokerto, 2023)
The development of communication technology allows journalists to publish journalistic content independently through personal accounts on social media and sharing platforms. Independent publication allows journalists to earn additional income exceeding their official salary as journalists in media companies. This practice indicated as entrepreneurial journalism often blurs the boundaries between journalistic and commercial aspects. This study aims to reveal the meaning of entrepreneurial journalism among journalists of mass media companies. This study uses the social construction of technology (SCoT) theory with Alfred Schutz's phenomenological method and a qualitative approach. The study showed that journalists publish news through social media accounts and sharing platforms in various forms and content formats. The journalists practice entrepreneurial journalism because their skills support their passion for mastering technological devices. Besides, they also achieve self-satisfaction from working independently. Journalists regard entrepreneurial journalism as a side job while upholding the journalistic aspect rather than the economic reason. Expectations and opportunities to earn additional income do not attract journalists practicing entrepreneurial journalism to ignore journalistic values and norms. Journalists prioritize creating and publishing quality news content by following the Journalistic Code of Ethics. Entrepreneurial journalism tends to be interpreted by journalists personally as a form of repositioning and self-actualization during social life.